Factors Affecting Innovative Work Behavior of Employees in Local Administrative Organizations in the South of Thailand - Chatchawan, Rutchapong; Trichandhara, Kanon; Rinthaisong, Idsaratt (International Journal of Social Sciences and Management, 2017)
This study aimed to develop a conceptual framework of factors affecting innovative work behavior of employeers in local administrative organizations. The study was conducted through a review of literature and document analysis. The results were presented in a form of descriptive analysis. The results show that team climate inventory, learning orientation, organizational supoortiveness, and transformational leadership play a direct role in developing innovative work behavior. Meanwhile, organizational supportiveness indirectly affects team climate inventry and transformational leadership indirectly affects learning orientation. Int. J. Soc. Sc. Manage. Vol. 4, Issue-3: 154-157